2014
DOI: 10.1007/s00018-014-1796-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical regulation of macrophage phenotype and function

Abstract: Macrophages are tissue-resident immune cells that play a critical role in maintaining homeostasis and fighting infection. In addition, these cells are involved in the progression of many pathologies including cancer and atheroscloerosis. In response to a variety of microenvironmental stimuli, macrophages can be polarized to achieve a spectrum of functional phenotypes. This review will discuss some emerging evidence in support of macrophage phenotypic regulation by physical and mechanical cues. As alterations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
365
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(372 citation statements)
references
References 107 publications
6
365
1
Order By: Relevance
“…5c). The slowly accumulating insight into the molecular mechanisms of the mechano sensing 23,[104][105][106] will allow drugable, pharmacological targets to be identified in order to better avoid FBR-causing mechanosensitivity of cells in contact with an implant. Slow release of suitable agonists could then be built into the implant surface to mechanically silence the cells in contact with it (that is, pharmacological stealthing of the implant).…”
Section: Engineering the Local Mechanical Microenvironmentmentioning
confidence: 99%
“…5c). The slowly accumulating insight into the molecular mechanisms of the mechano sensing 23,[104][105][106] will allow drugable, pharmacological targets to be identified in order to better avoid FBR-causing mechanosensitivity of cells in contact with an implant. Slow release of suitable agonists could then be built into the implant surface to mechanically silence the cells in contact with it (that is, pharmacological stealthing of the implant).…”
Section: Engineering the Local Mechanical Microenvironmentmentioning
confidence: 99%
“…Studies have demonstrated that TLR4 and IFN-γ receptors on the macrophage can interact with the M1 activation signal, while IL-10R and IL-4R respond to the M2 activation signal [41]. Signaling pathways involved in macrophage polarization have been investigated (Figure 1).…”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…However, these macrophages exhibited a low expression of Arg1, which is not consistent with a typical M2 phenotype [107]. The discrepancies in these studies may be due to the inherent differences of the cell lines used in each study since macrophages from different species or anatomical sites are known to behave differently [108]. …”
Section: Biomaterials Strategies To Manipulate M1 Vs M2 Differentimentioning
confidence: 99%